The issue of the skeptical sources in the Renaissance: the case of Sanchez’s Quod nihil scitur - Bermúdez Vázquez, Manuel (Estudios de Filosofía, 2019)
Among the problems that contemporary research has had to deal with when analyzing the recovery of skepticism in the Renaissance, there is not only the question of the sources, but also the type of skepticism that these sources transmitted. In these pages we propose to revisit the question of the sources that influenced the writing of one of the fundamental works of Renaissance skepticism, Francisco Sanchez’s book That nothing is known.